THE MAPPING OF SHORELINE CHANGE BENGKULU CITY WATER’S - Kurniawati, Esty; Nedi, Syahril; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A mapping of shorlines change was conducted used by landsat 5 TM, 7 and 8 ETM+. The aim of this reseacrh was to made shorelines change map and to analyze the rate of shorelines change. The method used in this research was survey method. Image data obtained in September 2001, May 2006, May 2011 and January 2016 were analyzed in the SIG Laboratory, Fakulty of Fisheries and Marine Science, Riau University. Based on data analyzed, field study was conducted in May 2016 at Bengkulu City Water’s.The result of the study showed that the average accretion 3,6 meter/year was happen in Bengkulu city. The highest tide was found in station 2 (0,6 – 0,85 meter) and the lowest tide was found in station 3. Current velocity in the highest tide 0,3 meter/second and the lowest tide 0,32 meter/second. The turbidity of marine water 0,336 NTU - 4,08 NTU. The slope of the beach in Bengkulu city > 0 – 2 % with depth range 4 – 6 meter.Key word’s : Shorline cange, mapping, Bengkulu City Water’s.